Is The Desire to Take Selfies Related to Self-Esteem in High School Teens? - Windarwati, Heni Dwi; Ati, Niken Asih Laras; Ilmy, Shofi Khaqul; Sulaksono, Ari Dwi; Fitriyah, Erna Tsalatsatul; Kusumawati, Mira Wahyu; Fitri, Linda Dwi Novial (Jurusan Keperawatan FIKES UNSOED, 2021)
Selfitis is one of the phenomena that is currently popular among adolescents. Adolescents are attracted to show self-presentation, one of which is through selfies. This study aimed to identify the correlation between the obsessive desire to take selfies and high school adolescents' self-esteem. This research was a quantitative study with a cross-sectional design. The study population was high school adolescents aged 15-16 years with 797 participants recruited using a total sampling method. The instrument in this study used the Rosenberg self-esteem questionnaire to measure self-esteem and the Selfitis Behavior Scale (SBS) questionnaire to measure selfitis in adolescents. The results showed that most of the adolescents had borderline selfitis (46.3%) and high self-esteem (88.1%). Factors that were significantly related to taking selfies amongst adolescents were gender (p-value: 0.000) and socioeconomic status (p-value: 0.000). Meanwhile, gender (p-value: 0.013), socio-economic status (p-value: 0.032), family harmony (p-value: 0.000), and selfitis (p-value: 0.000) were significantly related to self-esteem in adolescents. The multivariate analysis results showed that harmony in the family was the most influential factor in adolescents' self-esteem. Adolescents with higher levels of selfitis and harmony in the family tended to have better self-esteem.